2017
DOI: 10.1002/aur.1842
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and functional and structural brain differences in middle‐age adults with autism spectrum disorder

Abstract: We compared cognitive abilities and brain measures between 16 middle-age men with high-functioning autism spectrum disorder (ASD) and 17 typical middle-age men to better understand how aging affects an older group of adults with ASD. Men with ASD made more errors on a test involving flexible thinking, had less activity in a flexible thinking brain network, and had smaller volume of a brain structure related to memory than typical men. We will follow these older adults over time to determine if aging changes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 88 publications
(124 reference statements)
6
74
1
Order By: Relevance
“…Thus, in older autistic men with a late adulthood ASC diagnosis and (above) average IQ, EF problems in daily life are clearly reported on, while this is not reflected in their cognitive test performance and is not differentially impacted by their age. The consistency of findings across the current study and the Davids et al (2016) study, is in sharp contrast with the lack of consistency across the broader range of studies including older autistic adults (Braden et al 2017;Geurts and Vissers 2012;Lever and Geurts 2016a, b;Powell et al 2017;Tse et al 2019;Walsh et al 2019). This inconsistency in findings could be due to differences in sample characteristics (age, sex, IQ level), type of cognitive tasks included, chosen statistical analyses, and how intelligence levels were accounted for.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Thus, in older autistic men with a late adulthood ASC diagnosis and (above) average IQ, EF problems in daily life are clearly reported on, while this is not reflected in their cognitive test performance and is not differentially impacted by their age. The consistency of findings across the current study and the Davids et al (2016) study, is in sharp contrast with the lack of consistency across the broader range of studies including older autistic adults (Braden et al 2017;Geurts and Vissers 2012;Lever and Geurts 2016a, b;Powell et al 2017;Tse et al 2019;Walsh et al 2019). This inconsistency in findings could be due to differences in sample characteristics (age, sex, IQ level), type of cognitive tasks included, chosen statistical analyses, and how intelligence levels were accounted for.…”
Section: Discussioncontrasting
confidence: 66%
“…Cognitive flexibility the digital version of the Wisconsin Card Sorting Task (WCST) was used (Berg 1948; the paper and pencil version was used in Braden et al 2017; the abbreviated version in Geurts and Vissers 2012). The WCST consists of four stimulus cards that vary along three dimensions (colour, shape, and number).…”
Section: Objective Ef Assessment: Neuropsychological Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the reviewed studies quantifying hippocampal volume, outlined in Supplementary Table 5, there were mixed findings regarding hippocampus volume differences in ASD patients, with 3 studies reporting a decrease in hippocampus volume in patients with autism (Braden et al, 2017; Eilam‐Stock et al, 2016; Yarkoni et al, 2011). One of these studies utilised the MAGeT‐Brain multi‐atlas segmentation approach, which has been shown to achieve more accurate hippocampal volumes than FreeSurfer or FIRST on an Alzheimer's disease dataset (Pipitone et al, 2014).…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%